Persistent Atrial Flutter Treated by Coronary Sinus Ablation in Persistent Left Superior Vena Cava - Andrea Giuseppe Porto; Sergio Conti (Clinical Case Reports)
ABSTRACT Ablation of atypical atrial flutter may be challenging, particularly when a complex substrate is present. The persistence of left superior vena cava and severe coronary sinus dilatation carries an arrhythmogenic potential. In this case of atrial flutter, extensive substrate and activation mapping revealed the critical substrate within the coronary sinus.